Association Between Systemic Immune‐Inflammation Index and Psoriasis, Psoriasis Comorbidities, and All‐Cause Mortality: A Study Based on NHANES - Yang Zhao; Yan Ping Bai; Lin Feng Li (Immunity, Inflammation and Disease)
Abstract Objective The relationship between systemic immune‐inflammation index (SII) and psoriasis and its prognosis is not yet clear. In this study, the correlation between SII and psoriasis, psoriasis comorbidities, and all‐cause mortality was investigated based on the National Health and Nutrition Examination Survey (NHANES). Methods The study population was derived from five NHANES cycles: 2003–2006, 2009–2014, and survival follow‐up was as of December 31, 2019. The association between SII and psoriasis and its comorbidities was analyzed using weighted multivariate logistic regression models. Weighted COX regression was used to calculate hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs). Restricted cubic spline, subgroup and sensitivity analyses were also used. Logarithmic conversion was performed on SII(log2SII) to reduce the impact of outliers. Results A total of 21,431 participants were included in this study. As a continuous variable, log2SII was significantly associated with psoriasis in the fully adjusted model [OR = 1.20(1.04–1.39), p = .01]. log2SII remained positively associated with psoriasis after excluding participants with a history of cancer or cardiovascular disease (CVD), or non‐Hispanic black participants. Among psoriasis patients, log2SII was significantly associated with metabolic syndrome (MetS) [OR = 1.68(1.19,2.38), p = .004] and all‐cause mortality [HR = 1.48(1.09,1.99), p = .01]. Similar results were consistently observed when SII was analyzed as a categorical variable (in quartiles). Conclusion This study suggested a positive association between SII and the prevalence of psoriasis. Among psoriasis patients, SII was positively correlated with MetS and all‐cause mortality.